FAKTOR PEMBENTUK KARAKTERISTIK KAWASAN RUANG JALAN H. RAIS A. RAHMAN Kelurahan Sungai Jawi Dalam Pontianak Kalimantan Barat - , SYAMSURIZAL ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Development of urban waterfront areas, especially in Indonesia is one of the potential and characteristics that must be developed, especially those dealing with aspects of functionality and accessibility. Development of urban waterfront areas, especially in Indonesia is one of the potential and characteristics that must be developed, especially those dealing with aspects of the function and aksesibelitas. Development of urban waterfront area can be directed to the development of the tourism function, economy, culture, education, industry, warehousing and defense. In its development the need for specific identification of the physical characteristics of the environment and its activities that take place therein. Sungai Jawi area is one area on the outskirts of the city of Pontianak on through by a river which empties into the great river of the Kapuas River. Sungai Jawi is one area that can potentially become an attractive residential area other than as a business and trade, as well as in its development found to the various problems that arise as a result of acculturation and socio-cultural changes in the original priority to transport water as aksesibelitas and is now replaced by ground transportation . The role of the river has decreased due to road construction as new transportation routes, changes in technology, behavioral and cultural change, this change is not just happening in developed countries but also have an impact on countries that while it is being developed especially in Asia and the cities waterfront in Indonesia in general. These changes not only alter the community's economy around Sungai Jawi, but this change also affects the shape and function of the building along the road space H Rais, A Rahman as the axis of Sungai Jawi area. Growth of new buildings to be out of control, no longer pay attention to the environmental situation around the road space, and the river became underdeveloped areas of the region. Formal and informal economic activities are scattered along the road space. with different activities in the morning as the trading and at night as the annual culinary culture interspersed with riverside community celebrations on the river along the road space. This study aims to provide a picture of the specific characteristics, problems and potentials in the development of waterfront cities in Indonesia in terms of physical parameters of environmental, economic, social and cultural as well as within a residential area and trading business.